Active Learning through PBL: A Quantitative Study in the Context of Merdeka Belajar. - Nurlindawati Amrain; Roy Hasiru; Agil Bahsoan; Meyko Panigoro; Yulianti Toralawe (Yayasan Pendidikan Sudirman Mandiri, 2026)
This study examines the impact of Problem-Based Learning (PBL) on Social Studies learning outcomes at SMP Negeri 1 Atinggola in North Gorontalo, Indonesia. Conducted over four months with 65 Grade VIII students, the research used a quantitative descriptive approach. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed with SPSS v20.0. Results show a positive and significant effect of PBL on academic achievement, with a t-count of 5.212 and R² of 0.301. The equation (Ŷ = 53.445 + 0.531X) indicates each increase in PBL implementation improved scores by 0.531 points. Students displayed greater motivation, participation, and engagement. Observations and interviews supported these findings, revealing enhanced autonomy and relevance of learning. This study confirms that PBL is an effective strategy for Social Studies, aligning with national curriculum goals like Merdeka Belajar and Profil Pelajar Pancasila. It offers practical insights for improving student-centered learning and contributes to research on active learning strategies.